Use of food resources by small fish species in Neotropical rivers: responses to spatial and temporal variations - Silva,Jislaine Cristina da (2014)
Spatial and temporal variations in food supply play a crucial role in the determination of the patterns of food use by fish species. This study evaluated spatial and temporal variations in food utilization by small fish species of the Verde River, Upper Paraná River Basin, state of Mato Grosso do Sul, Brazil. Samplings were conducted in the rainy and dry periods, from November 2010 to August 2012, using trawls, cast nets and gillnets, in nine sampling sites grouped into three biotopes: upstream and downstream of the Branca Waterfall, and tributary. The stomach contents of 3,263 individuals of 12 small species were examined according to the volumetric method. Altogether, 31 food items were identified. Overall seed consumption was greater in the rainy period, and the consumption of terrestrial plants was greater in the dry period. Hymenoptera was an important item in the diet, but the proportions in the consumption of this item was different between biotopes and periods. The consumption of Coleoptera and Isoptera was expressive only downstream of the Branca Waterfall in the rainy period, and aquatic plant was mostly consumed in the tributary in the dry period. Significant differences were detected in the diet composition between biotopes, hydrological periods and also the interaction between these two factors. Allochthonous resources were clearly the most consumed by the species in all biotopes, especially during the rainy period. The dietary overlap between species, although showing significant spatial and temporal differences, was low (0.4) for about 60% of species pairs. Thus, it is concluded that spatial and temporal changes in the utilization of food resources by small fish were related to physiographic differences of the channel and the surroundings, which contributed to the significance of seasonal changes in the diet, also reflecting the low dietary overlap between species.